The impact of seasonal hydrological disturbances on the presence and formation of toxic cyanobacteria blooms in coastal Louisiana - Hammond, Courtney Nicole; Bargu, Sibel; Turner, Caitlin R. R.; Hiatt, Matthew; White, John R. (Frontiers in Marine Science, 2025)
Estuaries in the Gulf, especially Lake Pontchartrain Estuary in southeastern Louisiana, USA, are experiencing significant changes due to climate change and coastal restoration efforts. Lake Pontchartrain Estuary receives nutrient-rich Mississippi River water through a controlled diversion called Bonnet Carré Spillway (BCS), which has been associated with toxic cyanobacterial blooms (cyanoHABs). This study examines the seasonal factors influencing cyanoHABs in the Lake Pontchartrain Estuary when the BCS is closed, addressing gaps in the understanding of HABs related to other physical drivers. Field samples collected in 2021, during the closure of the spillway, revealed significant evidence of seasonal variations in cyanoHAB formation. Results indicate that water leakage from the spillway and tributary discharge are critical for supporting cyanoHABs during the summer months. Moreover, nitrogen-fixing cyanobacteria, such as nitrogen-fixing Dolichospermum and Cylindrospermum, were more abundant following strong winds from significant weather events, including cold fronts and hurricanes, which can resuspend phosphorus that is bound to sediment. This research improves our understanding of the physical factors that drive the formation of cyanoHABs, the prevalence of different species, and the production of toxins in the Lake Pontchartrain Estuary. The insights gained from this study are essential for environmental managers to develop effective, long-term monitoring strategies for harmful algal blooms.